Análisis experimental de las características de emisión de motores diésel de baja cilindrada operando con mezclas de biodiésel de aceite de alga - Maestre-Cambronel, Daniel; Orjuela-Abril, Sofia; Duarte-Forero, Jorge Eliécer (Ingeniería, 2022)
Context: The imminent concern regarding greenhouse gas emissions associated with internal combustion engines has motivated both the industrial and academic sectors to propose reliable solutions in order to mitigate the adverse effects of thermal machines. Partial fuel substitution with biodiesel blends is a promising, convenient, and diverse technology that can contribute to minimizing emission levels. Method: This study incorporated an experimental test bench for a low-displacement diesel engine that enabled control of the operating conditions in order to evaluate thermal performance, fuel metrics, and emission levels. An algae oil biodiesel blend at replacement percentages of 5% (AB5) and 15% (AB15) was produced via a transesterification technique. The performance evaluation was centered on the impact of the variable compression ratio and torque ranges of the engine. Results: The implementation of algae oil as a biodiesel blend reduced the emission levels of CO, CO2, and HC by 40-95% compared to diesel standalone operation. In contrast, it boosted NOx emissions in a reasonable proportion (<45%). Further emission minimization of CO and HC could be reached by increasing the compression ratio, but CO2 and NOx emissions were negatively affected. Moreover, increasing the compression ratio intensified the combustion pressure while improving both fuel consumption and thermal performance. Contrarily, a higher algae oil content in the biodiesel blend reduced the in-cylinder pressure, thus increasing the fuel consumption and reducing the thermal performance. Conclusions: In conclusion, biodiesel implementation demonstrated to be a robust tool to mitigate the global emissions of the engine to a great extent. The negative results regarding thermal performance and fuel consumption are a consequence of the higher density and lower heating value. However, this can be partially offset by increasing the compression ratio of the engine. The exploration of hydrogen and hydroxy is strongly recommended to contribute to enhancing the overall performance of partial fuel substitution technologies.